2015
DOI: 10.1111/evo.12587
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of island floras challenges taxonomy‐based biogeographical models of speciation

Abstract: Using phylogenetic data from insular and mainland congeneric species, we show that all of the endemic species are derived from independent colonization events rather than in situ speciation. This is in sharp contrast to the results of a study carried out in a comparable system, Lord Howe Island (Australia), where as much as 8.2% of the plant species were the product of sympatric speciation. Differences in physiography and age between the islands may be responsible for the contrasting patterns of speciation obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
(71 reference statements)
3
17
1
1
Order By: Relevance
“…However, the phylogenetic placement of C. alfonsiana and C. weatherbyana was ambiguous (Trusty et al 2012). Using the same data set (but analyzed independently), Igea et al (2014) confirmed Trusty's (2012) results, including the ambiguous placement of C. alfonsiana and C. weatherbyana.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, the phylogenetic placement of C. alfonsiana and C. weatherbyana was ambiguous (Trusty et al 2012). Using the same data set (but analyzed independently), Igea et al (2014) confirmed Trusty's (2012) results, including the ambiguous placement of C. alfonsiana and C. weatherbyana.…”
Section: Introductionsupporting
confidence: 55%
“…The origin of species endemic to islands has long fascinated scientists (Wallace 1880;Keeley and Funk 2011;Tye and Francisco-Ortega 2011;Igea et al 2014). Recent phylogenetic studies have demonstrated that the closest relatives of some island endemics are not always from the mainland but rather from neighboring islands (Sato et al 1999;Motley et al 2005;Harbaugh and Baldwin 2007;Andrus et al 2009;Namoff et al 2010), emphasizing the contributions of both continents and islands to insular biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intense searches, very few case studies have been able to meet the rigorous criteria for demonstrating sympatric speciation in nature (Coyne and Orr 2004;Bolnick and Fitzpatrick 2007). Even in some of the more convincing examples that do meet these criteria, genomic data have revealed more complex evolutionary histories of multiple colonization and repeated gene flow than previously assumed (Papadopolus et al 2011;The Heliconius Genome Consortium et al 2012;Geiger et al 2013;Alcaide et al 2014;Igea et al 2015;Malinsky et al 2015;Martin et al 2015a;Kautt et al 2016;Poelstra et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while knowledge about speciation on islands is constantly improving (e.g. Igea et al , 2015), future simulation studies could investigate to what extent radiation-proneness is lineage-specific (e.g. mediated by common traits).…”
Section: Discussionmentioning
confidence: 99%